KONTRIBUSI GURU PAK DALAM PEMBENTUKAN KEPRIBADIAN KRISTIANI SISWA DI SEKOLAH - Rianty Aminarty Tadu Lado; Harun Y. Natonis (CV. ADIBA AISHA AMIRA, 2025)
The role of Christian Religious Education (CRE) teachers is vital in shaping the Christian character of students within the school environment. This study explores the contributions of CRE teachers in fostering spiritual, moral, and social values rooted in Christian teachings. Through literature analysis and a descriptive approach, this research highlights how teachers become role models, facilitators of faith-based education, and mentors in guiding students toward living out Christian values in their daily lives. The findings indicate that CRE teachers contribute significantly to character development by integrating biblical principles into learning activities, building students' faith, and creating a school culture that upholds integrity, compassion, and responsibility. The study affirms the urgency of empowering CRE teachers to fulfill their spiritual and pedagogical duties effectively to shape a generation that reflects the image of Christ.